Analysis of serum transthyretin by on‐line immunoaffinity solid‐phase extraction capillary electrophoresis mass spectrometry using magnetic beads. Issue 9 (10th March 2016) - Peró‐Gascón, Roger; Pont, Laura; Benavente, Fernando; Barbosa, José; Sanz‐Nebot, Victoria
Abstract : In this paper, an on‐line immunoaffinity solid‐phase extraction capillary electrophoresis mass spectrometry (IA‐SPE‐CE‐MS) method using magnetic beads (MBs) is described for the analysis of serum transthyretin (TTR), which is a protein related to different types of amyloidosis. First, purification of TTR from serum was investigated by off‐line immunoprecipitation and CE‐MS. The suitability of three Protein A (ProA) MBs (Protein A Ultrarapid Agarose TM (UAPA), Dynabeads ® Protein A (DyPA) and SiMAG‐Protein A (SiPA) and AffiAmino Ultrarapid Agarose TM (UAAF) MBs to prepare an IA sorbent with a polyclonal antibody (Ab) against TTR, was studied. In all cases, results were repeatable and it was possible the identification and the quantitation of the relative abundance of the six most abundant TTR proteoforms. Although recoveries were the best with UAPA MBs, UAAF MBs were preferred for on‐line immunopurification because Ab was not eluted from the MBs. Under the optimized conditions with standards in IA‐SPE‐CE‐MS, microcartridge lifetime (>20 analyses/day) and repeatability (2.9 and 4.3% RSD for migration times and peak areas) were good, the method was linear between 5 and 25 μg/mL and LOD was around 1 μg/mL (25 times lower than by CE‐MS, ≈25 μg/mL). A simple off‐line sample pretreatment based on precipitation of the most abundant proteins with 5% (v/v) of phenol was necessary to clean‐up serum samples. The potential of the on‐line method to screen for familial amyloidotic polyneuropathy type I (FAP‐I), which is the most common hereditary systemic amyloidosis, was demonstrated analysing serum samples from healthy controls and FAP‐I patients.